Dependence of piglet productivity on the method of their castration with dry feeding method - D. V. Zhdanov; M. G. Povod; O. G. Mykhalko; B. V. Gutyj; H. I. Kalynychenko; T. V. Verbelchuk (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Гжицького. Серія: Сільськогосподарські науки)
The sex dependence of the productivity of surgically and immunologically castrated pigs was investigated during the suckling period, under the liquid feeding method and during the growth and fattening period under the dry feeding method commonly used in Ukraine. During the suckling period, no difference was found between castrated and non-castrated piglets in terms of average daily and absolute weight gain and, consequently, piglet weight at weaning. At the same time, the maintenance of the piglets in the group of castrated boars was 2.6 % worse than in the group of uncastrated boars. During rearing, uncastrated boars consumed 3.8 % more feed, had a 5.2 % higher growth rate, resulting in 5.2 higher absolute weight gain over 51 days of rearing, 4.3 % higher mass at the end of rearing and 4.2 % better coma utilisation, but had a 0.2 % higher proportion of dead animals and 66.7 % higher weight compared to surgically castrated piglets. During fattening, immunocastrated male pigs had a 5.1 % higher growth rate, reached a market weight of 120 kg 3.6 earlier, had 5.1 % higher absolute weight gains and a 4.9 % higher animal weight at the end of the fattening period. With the same daily feed consumption, they had a 4.6 % better feed payment in stages and a 15.8 % higher overall index of fattening quality. At the same time, this group of pigs showed a 41.6 % higher piglet loss and thus a 0.6 % lower survival rate, but a 14.7 % lower weight of the excreted animals compared to the surgically castrated animals and their counterparts. During the rearing and fattening period, immunocastrated pigs consumed 0.8 % more feed, grew 5.2 % faster, had a 4.2 % better feed conversion ratio and 5.2 % higher absolute weight gain, but a 0.8 % higher proportion of excreted animals and a 0.6 lower survival rate compared to surgically castrated animals.